In vitro cytotoxicity assessment of ulvan, a polysaccharide extracted from green algae - Alves, A. (2013)
Sustainable exploitation and valorization of natural marine resources represents a highly interesting platform for the development of novel biomaterials, with both economic and environmental benefits. In this context, toxicity data is regarded as a crucial and fundamental knowledge prior to any advances in the application development of natural derived polymers. In the present work, cytotoxicity of ulvan extracted from green algae Ulva lactuca was assessed by means of standard in vitro cytotoxicity assays. Fibroblast-like cells were incubated in the presence of this green algae’s polysaccharide, and cell viability was assayed through 3-(4,5-dimethylthiazol-2-yl)- 5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium test. In addition, double stranded DNA and total protein were quantified in order to assess cell number. In order to establish ulvan’s non-cytotoxic behaviour, the effect of this polysaccharide on cellular metabolic activity and cell number was directly compared to hyaluronic acid (HA), used as a non-cytotoxic control material. In this study, ulvan demonstrated promising results in terms of cytotoxicity, comparable to the currently used HA, which suggests that ulvan can be considered as non-toxic in the range of concentrations studied.